Gain-of-Function Variant p.Pro2555Arg of von Willebrand Factor Increases Aggregate Size through Altering Stem Dynamics - Huck, Volker; Chen, Po-Chia; Xu, Emma-Ruoqi; Tischer, Alexander; Klemm, Ulrike; Aponte-Santamaría, Camilo; Mess, Christian; Obser, Tobias; Kutzki, Fabian; König, Gesa; Denis, Cécile V.; Gräter, Frauke; Wilmanns, Matthias; Auton, Matthew; Schneider, Stefan W.; Schneppenheim, Reinhard; Hennig, Janosch; Brehm, Maria A. (Thrombosis and Haemostasis, 2021)
The multimeric plasma glycoprotein (GP) von Willebrand factor (VWF) is best known for recruiting platelets to sites of injury during primary hemostasis. Generally, mutations in the VWF gene lead to loss of hemostatic activity and thus the bleeding disorder von Willebrand disease. By employing cone and platelet aggregometry and microfluidic assays, we uncovered a platelet GPIIb/IIIa-dependent prothrombotic gain of function (GOF) for variant p.Pro2555Arg, located in the C4 domain, leading to an increase in platelet aggregate size. We performed complementary biophysical and structural investigations using circular dichroism spectra, small-angle X-ray scattering, nuclear magnetic resonance spectroscopy, molecular dynamics simulations on the single C4 domain, and dimeric wild-type and p.Pro2555Arg constructs. C4-p.Pro2555Arg retained the overall structural conformation with minor populations of alternative conformations exhibiting increased hinge flexibility and slow conformational exchange. The dimeric protein becomes disordered and more flexible. Our data suggest that the GOF does not affect the binding affinity of the C4 domain for GPIIb/IIIa. Instead, the increased VWF dimer flexibility enhances temporal accessibility of platelet-binding sites. Using an interdisciplinary approach, we revealed that p.Pro2555Arg is the first VWF variant, which increases platelet aggregate size and shows a shear-dependent function of the VWF stem region, which can become hyperactive through mutations. Prothrombotic GOF variants of VWF are a novel concept of a VWF-associated pathomechanism of thromboembolic events, which is of general interest to vascular health but not yet considered in diagnostics. Thus, awareness should be raised for the risk they pose. Furthermore, our data implicate the C4 domain as a novel antithrombotic drug target.
Keywords: von Willebrand factor; hypercoagulability; GPIIb/IIIa